CONSUMER BEHAVIOUR IN ONLINE SHOPPING ORGANIC FOOD DURING THE COVID-19 PANDEMIC IN SERBIA - Ćirić, Maja (Food and Feed Research, 2020)
The purpose of this paper was to determine whether the Covid-19 Pandemic influenced the change in the extent of online shopping organic food in Serbia and whether it led to a change in organic food consumer behavior. The survey was carried out in Serbia by using a questionnaire developed specifically for this purpose. Descriptive statistics and Chi-square test were used to analyze the data obtained from the survey. The results indicate that the Covid-19 Pandemic has influenced the increase in the percentage of consumers who purchase organic food online. Also, the changes in the type and volume of organic food consumption were identified. Besides, the consumption of organic food varied depending on the sociodemographic characteristics of consumers who purchased online.
Keywords: consumer behavior; organic food; online shopping; pandemic; COVID-19